(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2016)
This paper examines the role of the Pilgrims Fund Board (Lembaga Tabung Haji, or THA) in its efforts to improve the economy, and hajj services for the Malays. The study is conducted through literature review, particularly the Annual Reports of the Pilgrim Fund Board. LTH was established to facilitate the Malays to gradually save money for the purpose of performing the hajj without the need to sell off property and thereby suffer hardship upon returning home from the Holy Land of Mecca. LTH is not only responsible for the welfare of the pilgrims in terms of health, transportation and accomodation but also the protection of the pilgrims from fraudulent practices and exploitation by unscrupulous parties. In the past, the Malays faced various difficulties in their endeavour to perform the hajj but with improved and more systematic hajj pilgrimage management, there was a gradual change for the better. Keywords: Lembaga Tabung Haji, Malays, Mecca, hajj, economy